The effect of e-commerce live streaming technical features on Chinese consumers' purchase intention-mediated by social support - Mengjia Qi; Janifer anak Lunyai (Environment and Social Psychology, 2025)
With the increasingly fierce competition in the online retail industry and consumers' increasing demand for online shopping experience, the existing marketing model is difficult to sustain and effectively attract consumers, and more e-commerce websites and sellers are trying to adapt to the ever-changing business environment through the introduction of new marketing models. Understanding the effect of e-commerce live streaming's influence on online purchasing intention can provide references and suggestions for e-commerce websites and sellers to give full play to the marketing value of live streaming and improve market competitiveness by doing so. Considering the interaction process between consumers and e-commerce live streaming platforms, we construct a relationship model between e-commerce live streaming technical features and online purchase intention based on the theory of "stimulus-organism-response". The study found that the real-time interactivity experience, perceived proximity, and authenticity of e-commerce live streaming positively influence consumer intention. By enhancing social support, these technical features further boost online buying interest. This study offers a technical review of the impact of the live streaming features on the consumer behaviour with the emphasis on the importance of the latter and provides insights into the optimal use of the resources allocation within the framework of e-commerce and live streaming technology.